DEVELOPMENT OF LEARNING DEVICES (LKS) BASED ON 5.0 USING THE WORD PRESS WEBSITE (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims to develop learning tools based on the WordPress website as an online learning resource that can be used in the learning process. This research is a research and development research that was developed through a WordPress-based LKS learning tool using an R&D model. The population of this research is the students of SMA Sesumatera Barat Class. This learning device development technique for LKS uses needs analysis, product design, development with a validation questionnaire by a team of experts, namely 2 material experts, 2 media experts, and 2 interpreters. Then the implementation, to obtain practicality responses, used a practicality questionnaire for 2 economics teachers and 25 students, with a practicality score of 99% for teachers and 99% for the rest in the very practical category. From the research results, it was found that the LKS learning tool was very feasible and very useful to use.